SYNTHESIS, STRUCTURAL ANALYSIS AND INITIAL ELECTRIC SCRATCHING ON PbZrXTi(1-X)O3 PIEZOELECTRIC MATERIAL - Syahfandi Ahda; Mardiyanto Mardiyanto; Parikin Parikin (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2018)
SYNTHESIS, STRUCTURAL ANALYSIS AND INITIAL ELECTRIC SCRATCHING ON PbZrXTi(1-X)O3 PIEZOELECTRIC MATERIAL. PbZrTi(1-x)O3(PZT) material is currently one of the highest- quality piezoelectric materials and has been widely used in various applications, including as sensors in the observation system in nuclear reactor cores. In this study, a solid state reaction method was used to synthesize PbZrTi(1-x)O3(PZT) material with variations in compaction pressure of 7000 and 5000 psi. The sample synthesized was analyzed by the crystal structure system using Rietveld method of X-ray diffraction (XRD) pattern. The fitting results from Highscore program showed compounds with perovskite crystals system of tetragonal (PbZr0.52Ti0.48O3) and rhombohedral (PbZr0,58Ti0,42O3) and PbTiO3 (tetragonal). The electrifying process using an electrical voltage of kv DC has been successfully carried out on synthesis products. The voltage source used is from the electronic circuit Television (TV) 14-21 inches which has a flyback component and then continues with a voltage drop by making a voltage divider. The polling results can be identified by measuring the piezoelectric constant with the d33 meter device. Optimization of polling parameters to the material temperature was obtained at 100 oC, then applied polling sample of PbZrTi(1-x)O3(PZT) material added by PVDF (1.5, 2.5 and 5% weight percent) to samples with the compaction of 7000 and 5000 psi. Maximum d33 measurement (61 x 10-12 C/N) was obtained on PZT material with a pellet pressure of 7000 psi. Increasing the addition of PVDF results in a reduction of d33.